PENINGKATAN KEMAMPUAN MENULIS PUISI DENGAN MENGGUNAKAN TEKNIK AKROSTIK PADA PESERTA DIDIK KELAS VIII B SMP NEGERI 1 WONOMULYO KEC. WONOMULYO KAB. POLEWALI MANDAR - Sulihin Azis (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2015)
This study was motivated low interest of learners in the writing of poetry, which is the learners who have difficulties to explore ideas in poetry writing, this can be seen from the average value of a minimum completeness criteria before.This study aims to describe the increase in the ability to write poetry using acrostic techniques learners VIIIB class SMP Negeri 1 Wonomulyo.Jenis research used in this research is classroom action research (PTK) with the study design planning, action, observation, and refleksi. Subject of this research is all class learners VIIIB SMP Negeri 1 Wonomulyo. Instrument of research in this study is to test and non-test, the test instrument is the result of the performance of learners in writing poetry while the instrument is in the form of sheets of non-test interview, observation, and dokumentasi. Based on statistical analysis results that have been conducted by the researchers, the values obtained in cycle I and cycle II. In the first cycle the average value of the learners is 74.74 and the second cycle the average value obtained learners are 78.97. Result of average ratadari each cycle has increased, it concludes that the use of the technique can improve the ability to write acrostic poems on VIIIB grade students of SMP Negari I Wonomulyo